First record of Gephyrocharax valencia (Characiformes: Characidae: Stevardiinae) from the island of Trinidad, West Indies - Vanegas-Ríos, James Anyelo (2013)
Fil: Vanegas-Ríos, James Anyelo. División Zoología de Vertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina